M. Kula from estate to cabinet - M. Kula Segaran (Strategic Information and Research Development Centre, 2019)
This is a rags to riches story of an estate boy whose determination to avert the limited prospects of people of his background led him to make good at his profession and go on to pursue a political career which led him to the top of Malaysian politics. From Estate to Cabinet is M. Kula's chronicle of his rise from an underprivileged existence to national prominence as a lawyer and politician, up to the beginning of Malaysia's 14th General Election. It's a story Malaysians will find interesting for they can easily identify with the episodes and experiences described in the book. As Lim Kit Siang says in the foreword, Kula's life is "quintessentially Malaysian" because it is a product of the Malaysian dream.